BPEL cookbook : best practices for SOA-based integration and composite applications development : ten practical real-world case studies combining business process management and web services orchestration /: best practices for SOA-based integration and composite applications development : ten practical real-world case studies combining business process management and web services orchestration. (2006) - Unknown
No abstract available